Effect of heat treatment on morphology of Fe-rich intermetallics in Al–Cu alloys. Issue 6 (13th April 2017) - Lin, B.; Zhang, W. W.
Abstract : The iron-rich intermetallics are considered to be stable in aluminium alloys and usually hard to dissolve into the matrix during solution heat treatment (SHT). Nevertheless, solid-state transformations between Fe-rich intermetallics may happen and will play a great role in breaking-up of the large Fe-rich intermetallics particle during hot deformation process. In this study, the solid-state phase transformation of the iron-rich intermetallics from Alm Fe to β-Fe (Al7 Cu2 Fe) has been studied using SEM, XRD and deep-etched technique in a 2xxx Al–Cu cast alloy during SHT. The mechanism of solid-state transformation for the Fe-rich intermetallics was discussed, including the solid-state reaction, nucleation and growth of iron-rich intermetallics and Al phases.